2016
DOI: 10.1109/joe.2015.2429231
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the Wake Downstream of a Horizontal Axis Tidal Turbine Using a Modified Vorticity Transport Model

Abstract: Vybulkova, L., Vezza, M., and Brown, R. (2016) Simulating the wake downstream of a horizontal axis tidal turbine using a modified vorticity transport model. IEEE Journal of Oceanic Engineering, 41(2), pp. 296-301.There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it.http://eprints.gla.ac.uk/119684/ In order to decrease the need for fossil fuels, the alternative energy resources must be not only economically viabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…11c). The channel bed induced turbulence aids in entraining fluid into the wake and this is in line with the findings by Vybulkova et al [48] who investigated the effects of a parabolic approach flow velocity distribution on the wake of a HATT in comparison with an uniform approach flow.…”
Section: Effect Of Free-stream Turbulence On Rotor Hydrodynamicssupporting
confidence: 88%
“…11c). The channel bed induced turbulence aids in entraining fluid into the wake and this is in line with the findings by Vybulkova et al [48] who investigated the effects of a parabolic approach flow velocity distribution on the wake of a HATT in comparison with an uniform approach flow.…”
Section: Effect Of Free-stream Turbulence On Rotor Hydrodynamicssupporting
confidence: 88%
“…The vortex three-dimensional flow features are similar to those described by Leishman (2006), Pinon et al (2012), andMason-Jones et al (2013). The inclination of the helical structures has been attributed to the effect of the sediment bed (Vybulkova, 2013;Vybulkova et al, 2016), and also to an upward flow behind the turbine (Mason-Jones et al, 2013). Regarding asymmetries, several studies have found clear differences although not much attention has been given to them.…”
Section: Discussionsupporting
confidence: 71%
“…Fletcher and Brown, 2008;Houston and Brown, 2003;Green et al, 2005), wind turbines (e.g. Fletcher and Brown, 2010;, and tidal turbines (Vybulkova et al, 2016).…”
Section: Numerical Modellingmentioning
confidence: 99%
“…Equation is governed by the vorticity transport equation 17 . Then, the cost function to be minimised is given by ( ) ( )…”
Section: Mathematical Formulation 31 Semidefinite Programming Formulationmentioning
confidence: 99%